2017
DOI: 10.1039/c7em00245a
|View full text |Cite
|
Sign up to set email alerts
|

Source tracing of natural organic matter bound mercury in boreal forest runoff with mercury stable isotopes

Abstract: Terrestrial runoff represents a major source of mercury (Hg) to aquatic ecosystems. In boreal forest catchments, such as the one in northern Sweden studied here, mercury bound to natural organic matter (NOM) represents a large fraction of mercury in the runoff. We present a method to measure Hg stable isotope signatures of colloidal Hg, mainly complexed by high molecular weight or colloidal natural organic matter (NOM) in natural waters based on pre-enrichment by ultrafiltration, followed by freeze-drying and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
90
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 93 publications
(98 reference statements)
13
90
2
2
Order By: Relevance
“…However, under different flow paths such as runoff vs. baseflow, the exact source(s) of Hg can vary. It should be noted that mobilization of Hg associated with DOM can occur through the release of DOM-Hg complexes from soil OM without inducing additional MDF (Jiskra et al 2017). The binary mixing model results show that Hg in soil and river water is mainly derived from previous dry deposition into the watersheds, which is consistent with other studies in vegetated ecosystems examining both soil (Demers et al 2013;Enrico et al 2016;Obrist et al 2017) and surface-water samples (Jiskra et al 2017;Woerndle et al 2018).…”
Section: Transport and Sources Of Mercury In Riverssupporting
confidence: 89%
See 1 more Smart Citation
“…However, under different flow paths such as runoff vs. baseflow, the exact source(s) of Hg can vary. It should be noted that mobilization of Hg associated with DOM can occur through the release of DOM-Hg complexes from soil OM without inducing additional MDF (Jiskra et al 2017). The binary mixing model results show that Hg in soil and river water is mainly derived from previous dry deposition into the watersheds, which is consistent with other studies in vegetated ecosystems examining both soil (Demers et al 2013;Enrico et al 2016;Obrist et al 2017) and surface-water samples (Jiskra et al 2017;Woerndle et al 2018).…”
Section: Transport and Sources Of Mercury In Riverssupporting
confidence: 89%
“…Recent studies measuring the natural abundance of Hg stable isotope ratios have shown that the source(s) of Hg in surface water can be constrained by examining the isotopic composition of aqueous Hg. Both MDF and odd-MIF can vary depending on the hydrological conditions and atmospheric deposition of Hg in the watersheds (Jiskra et al 2017;Woerndle et al 2018). Thus, Hg isotope analyses may potentially help distinguish changes in the source(s) of Hg during extreme flooding events in blackwater river ecosystems if water sampling is conducted during the period of rapid changes in river hydrographs (Phillips and Slattery 2007;Majidzadeh et al 2017).…”
mentioning
confidence: 99%
“…Although the short‐term (1–2 years) decomposition period does not infer long‐term accumulation trend, the continual coverage of newly deposited litter can block external Hg uptake by the decomposing litter underneath (X Wang, Lin, et al, ) and possibly cause Hg loss in the decomposing litter through C and N mineralization. Reemission of Hg 0 by biologically mediated reduction can lead to a positive shift of δ 202 Hg on forest floor without significant MIF (M. Jiskra et al, , ; Kritee et al, , ; Woerndle et al, ). The more positive δ 202 Hg (~1–1.5‰ shift) in surface soil than in fresh litter confirms such Hg loss during long‐term litter decomposition mediated biologically because of negligible MIF shifts (Figures a–d).…”
Section: Resultsmentioning
confidence: 99%
“…It has long been suggested that OM mediates the transport of Hg from terrestrial to the adjacent aquatic environment. Negatively charged surfaces of OM are enriched with carboxyl functional groups (RCOO − ), and thiolates (RS − ) in OM behave as ligands to form a transition metal thiolate complex, which leads to a strong binding affinity with trace metals including Hg [34][35][36] . These associations among OM, thiolates, and THg contents can explain the positive relationships among them as observed in the Svalbard fjords ( Fig.…”
Section: Discussionmentioning
confidence: 99%